Implementasi Permainan Dalam Pembelajaran Oleh Calon Guru Guna Menghilangkan Kesan Kaku Dari Fisika - Al Arifin, Dedy Hidayatullah (Universitas Hamzanwadi, 2018)
Many theories of learning are appear from education experts. Not just environmental education in formal schools that make students understand the science. Instill a sense of love, happy, interested, and need to students is one of the effective tips for the success of learners. Teachers should be able to change the atmosphere of a stiff or lesson class becomes more enjoyable. By offering a lighter atmosphere and pleasant feel would give a positive effect on learners. The aim of this study is to change the view that physics was stiff and boring into physics fun through games in learning physics. The benefits of this research is to give response to prospective physics teachers to be able to give a pleasant impression on the subjects of physics. Result of this research is the implementation of the learning game physics can drop the impression of stiffness of physics teacher. It is shown by the percentage of students who apply games in physics have motivation 79.5% better than the control group that had motivated 68.375%. In addition, 76.5% of students responded positively to teach prospective physics teachers in implementing the learning game physics, while the group that did not apply in the learning game physics only 68.625%.